Children’s development of humour in everyday interactions: two case studies in French and Brazilian Portuguese - Del Ré, Alessandra [UNESP]; Dodane, Christelle; Morgenstern, Aliyah; Vieira, Alessandra Jacqueline (Estonian Literary Museum Scholarly Press, 2020)
In order to understand how children learn to recognize and use humour in their own cultural environment, we have chosen to study their production in two different languages and cultures. We studied a French-speaking monolingual child and a Brazilian Portuguese-speaking child, video-recorded once a month up to seven years old. The detailed multimodal linguistic coding of our data enabled us to draw the multimodal paths the two children followed from the first instances of shared amusement initiated by the adult, expressed mainly through reactive behaviour such as laughing, to the children’s own verbal production of successful humour in dialogue. Our study demonstrates that the production of children’s humour is closely linked to the family input (their micro-culture), and to children’s multimodal linguistic and meta-cognitive development. We did not observe important differences between the two children at the macro-cultural level, but there were noticeable inter-individual differences.
Keywords: Brazilian; children,; development; French; humour; microculture.